2018
DOI: 10.1029/2018gl077928
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐Scale Measurements of Dipolarization Front

Abstract: Dipolarization front (DF)—a sharp boundary with scale of ion inertial length (c/ωpi) in the Earth's magnetotail—can also have fine structures at electron scale (c/ωpe). Such electron‐scale structures, determining the local energy conversion, have not been revealed by multispacecraft observations so far, due to the large separation of spacecraft in previous studies. Here we report the first electron‐scale multispacecraft measurements of DF, using data from the recent Magnetospheric Multiscale mission. We find s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 67 publications
(145 reference statements)
10
72
0
Order By: Relevance
“…As can be seen, inside the electron jet, both energy conversion (see red line in Figure g) and energy dissipation (see red line in Figure h) were primarily negative, indicating an energy transfer from particles to electromagnetic field. The magnitude of maximum energy dissipation reached 2 nW/m 3 (Figure h), much larger than that at dipolarization fronts (Angelopoulos et al, ; Huang et al, ; Liu, Fu, Vaivads, et al, ; Liu, Fu, Xu, et al, ; Yang et al, ). Since the current was primarily from electrons, the energy dissipation in this event was driven by electrons.…”
Section: Observationsmentioning
confidence: 83%
“…As can be seen, inside the electron jet, both energy conversion (see red line in Figure g) and energy dissipation (see red line in Figure h) were primarily negative, indicating an energy transfer from particles to electromagnetic field. The magnitude of maximum energy dissipation reached 2 nW/m 3 (Figure h), much larger than that at dipolarization fronts (Angelopoulos et al, ; Huang et al, ; Liu, Fu, Vaivads, et al, ; Liu, Fu, Xu, et al, ; Yang et al, ). Since the current was primarily from electrons, the energy dissipation in this event was driven by electrons.…”
Section: Observationsmentioning
confidence: 83%
“…The intense electric fields at the JF, with both N and M components dominant (Figure c), exhibit spiky features. Such features are due to the ripples generated by lower hybrid drift instability, which is driven by density gradient at the front (Liu, Fu, Xu , et al, ; Pan et al, ). Sharp changes in the electron and ion distributions are observed at the JF crossing.…”
Section: Observationsmentioning
confidence: 99%
“…Now we focus on the flux pileup region behind the JF, where large‐amplitude E M and E L components are observed. The persistent E M ~ V N × B L is the motional electric field arising from the enhanced magnetic field strength and high‐speed flow (Fu et al, ; Liu, Fu, Xu , et al, ). The short‐period intense E L ~ E ∥ is the parallel electric field as the angle between the L direction and the local B is less than 3°.…”
Section: Observationsmentioning
confidence: 99%
“…The dipolarization front (DF), characterized by a sharp increase of magnetic field Bz (Fu et al, ; Liu, Fu, Xu, et al, ; Nakamura et al, ; Runov et al, ) and typically preceded by a small Bz dip structure (Schmid et al, ; Yao et al, ), is frequently observed in the Earth's magnetotail associated with bursty bulk flows (Fu et al, ; Liu et al, ; Schmid et al, ). It plays an important role in the energy conversion (Angelopoulos et al, ; Huang et al, ; Liu, Fu, Vaivads, et al, ), particle acceleration (Fu et al, ; Zhou et al, ), and transport of mass and magnetic fluxes (Liu et al, ; Nakamura et al, ).…”
Section: Introductionmentioning
confidence: 99%